PEMIKIRAN KRITIK SANAD HADIS - Hery Sahputra (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
Hadith sourced from the Prophet Muhammad in the form of words, deeds and takrir. Hadith can be accepted as dalil in Islam, if the Hadith meets the criteria of Sahih Hadith or Hasan Hadith. This status is determined by the sanad and eyes of a Hadith. The function of Hadith as the second source of Islamic law aims to describe everything that is conveyed in the Koran which is global, vague and concise. Therefore, the Koran and hadith become a unified guideline for Muslims.According to the Decree of the scholars and critics of Hadith, a hadith can be c to be valid in terms of sanad, if it is continuous with its sanad, fairness, dabit, safety and prevention of Hadith and its narrators from syaz and 'illat. Meanwhile, from an observational perspective, a hadith must not contradict the Koran, with a stronger Hadith, historical facts and common sense. Hadith is an explanation of the Koran, so the authenticity of Hadith is very necessary both in terms of sanad and matan. The position of Hadith as the second source of law requires a very deep research to avoid forgery in a Hadith.